Hierarchical Manufacturing of Anisotropic and High-Efficiency Electromagnetic Interference Shielding Modules for Smart Electronics - Shi, Shaohong; Deng, Siwen; Jiang, Yuheng; Chen, Jiabin; Sporrer, Lukas; Cheng, Fangchao; Guo, Quanquan; Jing, Jingjing; Chen, Yinghong (Nano-Micro Letters, 2026)
To shield electronics from complicated electromagnetic environments caused by wireless electromagnetic waves, achieving elaborately structural manufacturing while not sacrificing electromagnetic interference shielding performances remains crucial challenges. Herein, we propose a hierarchical manufacturing method that combines the use of 3D printing shear flow field and layer-by-layer assembly for fabricating the structurally customizable and multifunctional polylactic acid@graphene nanoparticle (PLA@GNs) materials. The dynamic behavior of polymer fluids is firstly explored via computational fluid dynamic simulation, and a Weissenberg number is employed to quantitatively analyze the disordered-to-ordered structural evolution of molecular chains and nanoparticles, allowing to tailor the micro-scale ordered structures. Subsequently, the macro-scale 3D architectures of PLA@GNs modules are fabricated by layer-by-layer assembly. Owing to the aligned GNs, the shielding performance reaches 41.2 dB, simultaneously accompanied by a directional thermal conductivity of 3.2 W m−1 K−1. Moreover, the potential application of 3D-printed shielding modules in specific civilian frequency bands such as 4G (1800–2100 MHz), Bluetooth (2402–2480 MHz), and 5G (3300–3800 MHz) is fully demonstrated. Overall, this work not only establishes a universal methodology about 3D printing shear flow field-driven orientation of two-dimensional nanoparticles within polymer fluids, but also gives a scientific method for advanced manufacturing of the next-generation electromagnetic functional modules for smart electronics. Highlights: 1 A universal methodology regarding 3D printing shear flow field-driven orientation of two-dimensional graphene nanoparticles within polymer fluids is established via computational fluid dynamics simulation. 2 A hierarchical manufacturing strategy is purposed to assembly polylactic acid@graphene nanoparticle (PLA@GNs) modules with anisotropic structural characteristics for contributing on the electromagnetic compatibility and heat dissipation of electronics. 3 The exceptional functionalities of 3D-printed modules including high-efficiency Electromagnetic shielding performance (41.2 dB) and directional thermal conductivity (3.2 W m−1 K−1) are achieved.